Error Patterns in Solving Ordinary Differential Equations: A SOLO Taxonomy-Based Analysis of Pre-Service Mathematics Teachers - Novitasari, Dwi; Pramestie Wulandari, Nourma; Lu’luilmaknun, Ulfa (FKIP Universitas Mataram, 2025)
This study aims to analyze students' errors in solving Ordinary Differential Equations (ODE) problems based on the SOLO taxonomy (Structure of the Observed Learning Outcome). This qualitative descriptive research involved 29 students from the Mathematics Education Study Program at the University of Mataram. Data were collected through essay tests and interviews, then analyzed using the SOLO taxonomy classification and error types based on the framework by Subanji and Mulyoto. The results show that most students were at the pre-structural, uni-structural, and multi-structural cognitive levels, with a dominance of conceptual and technical errors. Common mistakes included the use of incorrect formulas, errors in algebraic manipulation, and weak fundamental calculus skills. A lack of understanding of prerequisite concepts such as algebra and calculus was identified as the main factor contributing to these errors. These findings highlight the importance of strengthening basic concepts and implementing learning strategies based on the SOLO taxonomy to improve students' understanding of ODE topics